Exploratory Factor Analysis of Students' Responses to the Dhysning (Dynamic Hybrid System for Integrating Glocal Wisdom) Application for Teaching Science Literacy Skills - Alhusni, Hanan Zaki; Prahani, Binar Kurnia; Sunarti, Titin; Jatmiko, Budi; Citra, Nina Fajriyah; Kurtuluş, Muhammed Akif; Nugroho, Yuli Sutoto; Bunyamin, Muhammad Abd Hadi (JPPS (Jurnal Penelitian Pendidikan Sains), 2025)
Objective:  This study aims to develop and evaluate the effectiveness of the Dhysning (Dynamic Hybrid System for Integrating Glocal Wisdom) application, which integrates the local wisdom of the Boranan Lamongan Dance into physics learning, specifically on the topic of rigid body equilibrium. Method: The development of the Dhysning application followed the ADDIE model (Analysis, Design, and Development). The application was designed using Adobe Flash CS6 and included teaching modules, interactive multimedia, student worksheets, virtual laboratory simulations, and quizzes. The research was conducted through a limited trial involving three classes and three physics teachers at senior high school. Data were collected through response questionnaires and analyzed using descriptive statistics and Exploratory Factor Analysis (EFA) to examine the construct validity and reliability of student responses. Results: The results show that the application effectively supports science learning with strong student engagement. The Kaiser-Meyer-Olkin (KMO) measure of 0.638 and Bartlett's test of significance (p < 0.001) confirmed the suitability of the data for factor analysis. Eight factors were extracted, explaining 78.63% of the total variance, with an overall Cronbach's Alpha of 0.884, indicating high internal consistency. Students showed positive responses toward the contextual content, visual interactivity, and cultural relevance of the learning media. Novelty: This study introduces a glocalized science learning approach by incorporating regional cultural elements into physics education through interactive technology. It bridges local cultural identity with global scientific competencies, fostering deeper student engagement and scientific literacy in a unique and meaningful way.